A Hill Muscle Actuated Arm Model with Dynamic Muscle Paths - Penner, Johann; Leyendecker, Sigrid (Proceedings of the ECCOMAS Thematic Conference on Mutlibody Dynamics, 2019)
This contribution presents the optimal control of a musculoskeletal multibody model with Hill muscle actuation and dynamic muscle paths. In particular, the motion of a human arm and its muscle paths is described via constrained variational dynamics. The optimal control problem in this work is based on the direct transcription method DMOCC, where the optimal control problem is discretised in time, and the resulting nonlinear constrained finite dimensional optimisation problem is solved. To take a step towards finding global or multiple minima, we utilize the Matlab multistart framework for global optimisation. With the help of an example, we outline a framework to find feasible solutions and analyse several minima to which the nonlinear programming solver converges.
CRIS-Team Scopus Importer:2019-07-09